The impact of anthropogenic pressure on the virological quality of water from the Tiber River, Italy. (20th August 2017) - La Rosa, G.; Sanseverino, I.; Della Libera, S.; Iaconelli, M.; Ferrero, V.E.V.; Barra Caracciolo, A.; Lettieri, T.
Abstract: The objective of the present study was to assess the occurrence of major waterborne enteric viruses (enterovirus, norovirus, adenovirus, rotavirus, hepatitis A and E virus) along the Tiber River in Italy, in areas affected by different kinds of anthropogenic pressure (agricultural, urban, industrial and pristine). Moreover, in light of the recent abundant detection of human bocavirus in urban wastewater samples in Italy, the occurrence of this virus was also assessed. Virus detection was based on nested PCR followed by sequencing, and on real‐time PCR. A correlation with anthropogenic pressure was observed. The urban and industrial areas were the most contaminated (100 and 75% of samples were positive for at least one virus respectively). The agricultural area was less contaminated, with 50% of samples positive. None of the samples collected in a pristine area were positive for viruses. The most frequently detected virus was human bocavirus, identified in 37·5% of samples, followed by norovirus and enterovirus (28% each) and adenovirus (21·6%). Rotavirus, and hepatitis A and E viruses were less common (<9%). Although Human Bocavirus is not considered a waterborne pathogen, the widespread contamination of river waters suggests that virus transmission via the water route should not be neglected. Significance and Impact of the Study: To the best of our knowledge, this study constitutes the first attempt to assess the occurrence of enteric viruses in river waters, in areas differentially influenced by anthropogenic pressure. Enteric viruses (enterovirus, norovirus, adenovirus, rotavirus, hepatitis A and E viruses, and bocavirus) were widespread in the industrial and urban areas, and were less frequently detected in the agricultural area. Interestingly, human bocavirus was the most frequently detected virus, outnumbering even adenoviruses, known to be widespread in water environments. The widespread presence of bocavirus in surface waters suggests that a potential role of water in its transmission should not be excluded. Abstract : Significance and Impact of the Study: To the best of our knowledge, this study constitutes the first attempt to assess the occurrence of enteric viruses in river waters, in areas differentially influenced by anthropogenic pressure. Enteric viruses (enterovirus, norovirus, adenovirus, rotavirus, hepatitis A and E viruses, and bocavirus) were widespread in the industrial and urban areas, and were less frequently detected in the agricultural area. Interestingly, human bocavirus was the most frequently detected virus, outnumbering even adenoviruses, known to be widespread in water environments. The widespread presence of bocavirus in surface waters suggests that a potential role of water in its transmission should not be excluded.